Tiktok Sebagai Medium Partisipasi Politik Generasi Z di Indonesia Perspektif Maqasid Syariah - Nur Padila; Annisa J; Nur Azizah; Kurniati Kurniati (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The development of information technology has transformed political participation, particularly among Generation Z in Indonesia. Social media platforms such as TikTok function not only as entertainment spaces but also as mediums for political participation, allowing users to express opinions, influence public discourse, and engage with political content creatively. This study aims to analyze the essence of political participation in the digital space of TikTok, the mechanisms of digital political participation through the platform, and provide solutions based on the perspective of Maqasid Shariah. The research employs a qualitative descriptive approach, utilizing literature review and content analysis. The findings indicate that TikTok serves as an interactive and visual tool for political participation, yet it also carries potential negative impacts such as the spread of misinformation and social polarization. From the perspective of Maqasid Shariah, it is crucial to uphold public welfare, prevent harm (mafsadah), and prioritize ethical values in digital political engagement. This study recommends enhancing digital literacy and political ethics grounded in Maqasid Shariah principles to optimize Generation Z’s political participation on TikTok.